The College Aid Quandary: Access Quality and the Federal Role - Gladieux, Lawrence; Hauptman, Art (Rowman & Littlefield Publishers, 2011)
Each year, millions of American families struggle with the expense of higher education. For the past fifty years, the U.S. government has helped students and families pay for college; but with the entire domestic policy agenda in flux, federal aid to education hangs in the balance. This book analyzes government policies for helping students pay for education beyond high school. It is being published at a time when aid to education is a prominent issue in battles over the federal budget and policymakers are debating the need for and effectiveness of federal student assistance programs. Starting with the post-World War II GI Bill, the book reviews the 50-year history of federal student aid legislation, assesses the results, and identifies trends and problems that cloud the future of this critically important national effort. The authors draw on the thinking of the country's top experts in examining the rationale and structure of the student aid system and how it might more effectively expand college opportunities while ensuring educational quality. Their analysis encourages policymakers to consider the multiple objectives of government aidnot just getting more students into college, but promoting student success and degree completion. The book offers a framework for future policy debates aimed at improving a system vital to America's economic future and its continued promise of opportunity. Copublished with the College Board / Dialogue on Public Policy